2022
DOI: 10.1155/2022/6402646
|View full text |Cite|
|
Sign up to set email alerts
|

Application Value of Contrast-Enhanced Ultrasound Combined with Enhanced MR Scanning in Patients with Intrahepatic Cholangiocarcinoma

Abstract: Objective. To explore the clinical application effect of contrast-enhanced ultrasound (CEUS) combined with enhanced MR scanning in patients with intrahepatic cholangiocarcinoma (ICC). Methods. 90 patients with ICC admitted to Ganyu District People’s Hospital of Lianyungang City from June 2017 to June 2018 were selected as the research objects and randomly divided into control group and experimental group, with 45 cases in each group. The control group was tested by CEUS, and the experimental group was tested b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%